A FEASIBILITY STUDY FOR THE usE OF MOLECULAR MARKERS (RAPDs) FOR SALINITY TOLERANCE - Khan, Asif Ali; Tomestt, A B; McNeilly, Thomas (Biological Sciences - PJSIR, 2002)
A feasi bi l i ty study was ca rri ed ou t for t he use of molecu lar markers (R APDs) for sali nity tolerance i n maize. Pol ymorphism was sought i n two sal t toleran t accessions and a small sample of their F, progeny u si ng a l i mi ted nu mber of random pri mers. Whi l st, a considerable l evel of polymorphi sm wa s found u si;g only 4 primers , to make any concl u si ve rem arks about the suit abil ity of RAPD markers in the genetic anal ysi s of sali nity tolerance i n maize based on the l i mited data perh aps w ould be i n appropri ate. The R APD PCR amplification s were extrem el y sensiti ve and a si ngl e change i n th e concent ra t i on of reaction com ponent and/or thermal cycling parameters appeared to be altering th e R APD pattern s. Nevertheless, once optimised, the t echni que has the potent ial of prov iding an effecti ve and convenient meth od to gen erate molecular m arkers, which could be u tili sed i n mark aided selection of complex traits like sal i nity tolera nce.